Human capital effects on business organizations: econometric estimates for new businesses and exports - Marín Hernández, Marlit (2020)
Objective: to show the positive impact of human capital about new businesses and the levelof exports. Method: a literature review is done and after empirically two panel data modelsare estimated to measure the impact of human capital on business economic variables.Results: It was found that the public spending on education has a positive marginal effecton the generation of new businesses and the exports. For its part, investment in secondaryeducation has positive and significant effects on new business ventures, being secondaryeducation appropriate to generating an entrepreneurial behavior in young people. For theirpart, all education variables had positive and significant impacts on exports. Conclusions:it could be possible to find positive effects of human capital, especially in education, aboutthe creation of new businesses and over exports.